2020
DOI: 10.1136/heartjnl-2020-317393
|View full text |Cite
|
Sign up to set email alerts
|

Risk of severe COVID-19 disease with ACE inhibitors and angiotensin receptor blockers: cohort study including 8.3 million people

Abstract: BackgroundThere is uncertainty about the associations of angiotensive enzyme (ACE) inhibitor and angiotensin receptor blocker (ARB) drugs with COVID-19 disease. We studied whether patients prescribed these drugs had altered risks of contracting severe COVID-19 disease and receiving associated intensive care unit (ICU) admission.MethodsThis was a prospective cohort study using routinely collected data from 1205 general practices in England with 8.28 million participants aged 20–99 years. We used Cox proportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
259
2
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 325 publications
(299 citation statements)
references
References 27 publications
16
259
2
8
Order By: Relevance
“…Another study in France by Liabeuf [21]. Interestingly, in another large cohort study from the UK, Black Africans on ACEI/ARB were found to have higher risk of COVID-19 disease [50]. Our population may be considered similar to a study conducted in Turkey [51].…”
Section: Discussionsupporting
confidence: 65%
“…Another study in France by Liabeuf [21]. Interestingly, in another large cohort study from the UK, Black Africans on ACEI/ARB were found to have higher risk of COVID-19 disease [50]. Our population may be considered similar to a study conducted in Turkey [51].…”
Section: Discussionsupporting
confidence: 65%
“…(19) Most recently, a prospective cohort study using data from general practices in England found that use of ACE inhibitors or ARBs was associated with a significantly reduced risk of COVID-19 but not associated ICU admission. (33) This study also found that ethnicity modified the association between use of RAS inhibitors and COVID-19, with those from Black ethnic groups being at increased risk, a trend we were not able to explore in our study.…”
Section: Ace2 Expression(22)(10)contrasting
confidence: 54%
“…The country-cluster analysis is not well-suited to answer this question, and more studies among different ethnic groups are needed. For example, in a large cohort in the UK, it was found that Blacks being treated with ACEI/ARB were more susceptible to COVID-19 compared to Whites [21].…”
Section: Discussionmentioning
confidence: 99%